The X-ray structure determination of bovine carbonmonoxy hemoglobin at 2.1 Å resoultion and its relationship to the quaternary structures of other hemoglobin crystal forms - Safo, Martin K. (Cold Spring Harbor Laboratory Press, 2001)
Crystallographic studies of the intermediate states between unliganded and fully liganded hemoglobin (Hb) have revealed a large range of subtle but functionally important structural differences. Only one T state has been reported, whereas three other quaternary states (the R state, B state, and R2 or Y state) for liganded Hb have been characterized; other studies have defined liganded Hbs that are intermediate between the T and R states. The high-salt crystal structure of bovine carbonmonoxy (CO bovine) Hb has been determined at a resolution of 2.1 Å and is described here. A detailed comparison with other crystallographically solved Hb forms (T, R, R2 or Y) shows that the quaternary structure of CO bovine Hb closely resembles R state Hb. However, our analysis of these structures has identified several important differences between CO bovine Hb and R state Hb. Compared with the R state structures, the β-subunit N-terminal region has shifted closer to the central water cavity in CO bovine Hb. In addition, both the α- and β-subunits in CO bovine Hb have more constrained heme environments that appear to be intermediate between the T and R states. Moreover, the distal pocket of the β-subunit heme in CO bovine Hb shows significantly closer interaction between the bound CO ligand and the Hb distal residues Val 63(E11) and His 63(E7). The constrained heme groups and the increased steric contact involving the CO ligand and the distal heme residues relative to human Hb may explain in part the low intrinsic oxygen affinity of bovine Hb.